Palliative sedation at the end of life: Practical and ethical considerations - Caroline Barry; Robert Brodrick; Gurpreet Gupta; Imranali Panjwani (Clinical Medicine)
Sedation is commonly used at the end of life; however, there are several practical and ethical considerations for its use. It is important to identify any treatable causes for agitation prior to initiating medication. The drug, dose and route of administration may vary according to the indication for treatment, and specialist advice or supervision may be required. There are a number of ethical and cultural considerations relevant to the use of palliative sedation, which must also be understood to ensure best practice in this area.